The Yiddish presence in European literature : inspiration and interaction : selected papers arising from the Fourth and Fifth Mendel Friedman Conferences in Yiddish /: inspiration and interaction : selected papers arising from the Fourth and Fifth Mendel Friedman Conferences in Yiddish. ([2017?]) - Unknown
No abstract available